Evaluación de la variación de los parámetro para agua residual doméstica, en la interacción de macrofitas en una laguna de oxidación en el distrito de Soritor – Moyobamba - Rojas Ventura, Claudia Alexandra (2015)
The objective if this research was to determine the variation of the maximum allowable limits for domestic residual water due to the interaction of macrophytes in an oxidation lagoon. In this sense, are considered as parameters to the oils and fats, thermotolerant coliforms, the biochemical oxygen demand, chemical oxygen demand, pH, total suspended solids and the temperature of the domestic wastewater. According to the literature review was formulated the research hypotheses under the assumption that if they interact the macrophytes Typha angustifolia and Scirpus californicus in a lagoon of oxidation, then there will be significant changes in the maximum allowable limits for domestic residual water. In the methodological level~ the research was conducted under a design in randomized complete block considering a control treatment, a treatment with seedlings of Scirpus californicus and a treatment with Typha angustifolia. Likewise, there were considered to be three blocks for three measurements: to the first, second and third month. In the operative part, using a pump unit is ranked in each lagoon the domestic residual water from the oxidation ponds more nearby, obtaining in a systematic way a sample of a liter of water of each lagoon, each month for three months. This water was carried to the laboratory for analysis. With regard to the results and applying the Duncan test, with a confidence leve! of 95 %, it was demonstrated that the seedlings of Scirpus calijornicus and Typha angustifolia contribute significantly to decontaminate the domestic wastewater. As soon as the maximum allowable lirnits, in comparison to the initial state prior to the experiment, we conclude that the experiment with the macrophytes, the amount of oils and fats, thermotolerant coliforms, biochemical oxygen demand, chernical oxygen demand and total suspended solids although exceeds these limits, decrease significantly in relation to the control treatment. Key words: domestic residual water; oxidation lagoon